PENGELOLAAN KEUANGAN BISNIS - Fitri Nurhasanah; Wiranda Wiranda; Virnanda Bintang Syahputra (JIEKA: Jurnal Integrasi Ekonomi, Keuangan, dan Akuntansi, 2024)
Business financial management is an integral process that involves planning, organizing, directing, and controlling financial resources to achieve business goals, both short-term and long-term. This management includes various activities such as budgeting, investment, capital management, and financial reporting and evaluation. The main objectives of financial management are to maintain the company's financial stability, increase profitability, optimize capital use, minimize financial risk, and support the achievement of long-term goals. The main steps in business financial management include financial planning, systematic transaction recording, financial condition reporting, and control to ensure conformity between plans and actual results. Good financial management plays an important role in supporting business sustainability, increasing company value, and maintaining trust from internal and external parties. With effective management, businesses are not only able to achieve their economic goals but also have a positive impact on the welfare of society and the economic system as a whole.